Hubungan Psoriasis Dengan Komorbiditas Sistemik: Tinjauan Literatur - Wong, Hendra Wijaya; Kurniadi, Ivan; Yowen, Yowen (Universitas Kristen Krida Wacana, 2025)
Background: Psoriasis is a chronic inflammatory disease that not only affects the skin, but is also closely related to various systemic comorbidities. This literature review aims to examine the relationship between psoriasis and systemic comorbidities based on various recent studies. Methodology: Literature reviews made based on articles and journals are adjusted to the Inclusion and Exclusion Criteria. Journals were searched in medical databases through Pubmed, Google Scholar, Neliti, and Cochrane Library, using the keywords